Bollypolitics: popular Hindi cinema and Hindutva - Gehlawat, Ajay. (London Blommsbury Academic, 2024)
This book provides an in-depth exploration of the evolving landscape of Bollywood cinema in response to recent socio-political changes in India, including a surge in sectarian violence and the ascent of Hindutva, or Hindu nationalism, under Prime Minister Narendra Modi's leadership.
Keywords: Motion pictures India; Nationalism in motion pictures; Motion pictures- Political aspects India